ANATOMICAL CONSIDERATIONS ON THE ANNUAL SHOOT IN SOME WILD ROSES - Lidia ADUMITRESEI; Camelia Mariana IFRIM; Irina Neta GOSTIN (Journal of Plant Development)
The observations aim a comparative study of the anatomical structure of the stem and leaf, during anthesis, in some Rosa species and varieties (sports), in order to complete the data from the specialized literature because the morphological information is more numerous than the anatomical ones. Moreover, sometimes they are even inconsistent, as in the case of the glands/glandular trichomes on the leaves and stem. A series of similarities are highlighted, which can be considered conservative characteristics of the Rosa genus, as for instance: the rapid transition to the secondary structure, the disposition of the vascular bundles (of collateral type) on a circle, the absence of the phelloderm’s activity in the first year, the presence of the crystal idioblasts and the bifacial structure of the leaf. Also, a series of characteristics of each species is highlighted: disposition of the secondary xylem vessels, quantity of libriform fibres, the nature of the walls of the cells from the medullar rays, the thickness of the walls of the sclerenchyma fibres and the presence of the crystal idioblasts in various tissues.